Effects of flavonoids on vascular smooth muscle of the isolated rat thoracic aorta - Ajay, M.; Gilani, A.H.; Mustafa, Mohd Rais (Elsevier, 2003)
The potency, structure-activity relationship, and mechanism of vasorelaxation of a series of flavonoids, representing different subclasses (flavonols: fisetin, rutin, quercetin; flavones: chrysin, flavone, baicalein; flavanones: naringenin, naringin; isoflavones: diadzein and flavanes: epigallo catechin gallate), were examined in the isolated rat aorta. Most of the flavonoids tested showed concentration dependent relaxant effects against K +(80 mM) and phenylephrine (PE, 0.1 AM)-induced contractions with a greater inhibition of the responses to the a1-adrenoceptor agonist. The relaxant effects of most of the flavonoids involve in part the release of nitric oxide and prostaglandins from the endothelium as pretreatment with L-NAME and indomethacin attenuated the responses. In addition, the relaxant action of the flavonoids includes inhibition of Ca + 2 influx and release of Ca + 2 from intracellular stores. A structure-activity relationship amongst the flavonoids was suggested.